MENINGKATKAN KEMAMPUAN ANALITIK DAN AKTIVITAS SISWA SMP MELALUI PENERAPAN MODEL PEMBELAJARAN POE (PREDICTION, OBSERVATION, EXPLANATION) - Anis Prasetiyaningsih (JURNAL PEMBELAJARAN FISIKA, 2020)
The research about the implementation of POE (Prediction, Observation, Explanation) learning model to improve the student’s analytical thinking ability and student’s activities in the learning process. This research used Classroom Action Research (CAR). It consist of two cycles. The object of research was 32 students of VIII F SMPN 3 Jember in Academic Year 2019/2020. The research instruments are observation sheets, test of student’s analytical thinking ability. The result of the study showed that the use of learning model POE improve from cycle I to cycle II include (1) the student’s analytical thinking 73% in cycle I to 88 % in cycle II (2) there was the improvement of student’s activities 74.5 % (Good) in cycle I to 82,4 % (Very Good) in cycle II